2003
DOI: 10.1002/bsl.517
|View full text |Cite
|
Sign up to set email alerts
|

The verdict on jury trials for juveniles: the effects of defendant's age on trial outcomes

Abstract: With the progression to more adult-like policies and procedures for youth in the justice system, the right to a jury trial has been extended to young offenders. These youth would not be tried by a jury of their peers, however, but by a jury of adults. The concern is that adult jurors may hold negative attitudes about youth that might influence their decision making in a case involving a young defendant. Two studies examined whether and under what conditions defendant's age affects jurors' decisions about the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
48
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 36 publications
6
48
4
Order By: Relevance
“…These legislative changes, particularly with consistent emphasis on protecting society from dangerous juveniles who commit severe crimes, raise concerns of the fairness of trying juveniles in adult court. Juvenile defendants face a jury of adults who may hold biases that could influence verdict and sentencing decisions (Warling & Peterson-Badali, 2003). Empirical research has demonstrated that a wide variety of factors including defendant age, knowledge of a previous criminal history, crime type, and crime outcome may be influential for jury decisions for juvenile defendants in adult court (Ghetti & Redlich, 2001;Levine, Williams, Sixt, & Valenti, 2001;Rudebeck & Woody, 2002;Tang & Nunez, 2003;Warling & Peterson-Badali, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These legislative changes, particularly with consistent emphasis on protecting society from dangerous juveniles who commit severe crimes, raise concerns of the fairness of trying juveniles in adult court. Juvenile defendants face a jury of adults who may hold biases that could influence verdict and sentencing decisions (Warling & Peterson-Badali, 2003). Empirical research has demonstrated that a wide variety of factors including defendant age, knowledge of a previous criminal history, crime type, and crime outcome may be influential for jury decisions for juvenile defendants in adult court (Ghetti & Redlich, 2001;Levine, Williams, Sixt, & Valenti, 2001;Rudebeck & Woody, 2002;Tang & Nunez, 2003;Warling & Peterson-Badali, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These differences have necessitated additional investigation. Warling and Peterson-Badali (2003) examined the effects of the defendant's age on decisions about the guilt of and recommended sentences for a juvenile or adult defendant in adult court, and they concluded that the defendant's age does not impact jurors' verdicts. Sentence length varied with age, however, such that jurors assigned less severe sentences for younger defendants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations